Evolutionary computation in optimization and identification - Burczyński, Tadeusz; Beluch, Witold; Długosz, Adam; Kuś, Wacław; Nowakowski, Marek; Orantek, Piotr (Computer Assisted Methods in Engineering and Science, 2002)
The aim of the paper is to present the application of the evolutionary algorithms to selected optimization and identification problems of mechanical systems. The coupling of evolutionary algorithms with the finite element method and the boundary element method creates a new artificial intelligence technique that is very suitable in computer aided optimal design and defect detection. Several numerical examples for optimization and identification are presented.